Graft-Specific Surgical and Rehabilitation Considerations for Anterior Cruciate Ligament Reconstruction with the Quadriceps Tendon Autograft - Braidy Solie; Jill Monson; Christopher Larson (International Journal of Sports Physical Therapy)
Anterior cruciate ligament reconstruction (ACLR) with a bone-patellar tendon-bone (BPTB) or hamstring tendon (HT) autograft has traditionally been the preferred surgical treatment for patients returning to Level 1 sports. More recently, international utilization of the quadriceps tendon (QT) autograft for primary and revision ACLR has increased in popularity. Recent literature suggests that ACLR with the QT may yield less donor site morbidity than the BPTB and better patient-reported outcomes than the HT. Additionally, anatomic and biomechanical studies have highlighted the robust properties of the QT itself, with superior levels of collagen density, length, size, and load-to-failure strength compared to the BPTB. Although previous literature has described rehabilitation considerations for the BPTB and HT autografts, there is less published with respect to the QT. Given the known impact of the various ACLR surgical techniques on postoperative rehabilitation, the purpose of this clinical commentary is to present the procedure-specific surgical and rehabilitation considerations for ACLR with the QT, as well as further highlight the need for procedure-specific rehabilitation strategies after ACLR by comparing the QT to the BPTB and HT autografts.